Hospital inpatient in Indonesia: Does national health insurance matter? - Ratna Dwi Wulandari; Agung Dwi Laksono; Wahyu Pudji Nugraheni; Tati Suryati; Leny Latifah; Diah Yunitawati; Rofingatul Mubasyiroh; Irfan Ardani; Asep Kusnali; Abdullah Saleh Alruwaili (Clinical Epidemiology and Global Health)
Background: Hospitals are the final gate in Indonesia's health service system. Furthermore, the government's strategy to pursue universal coverage through National Health Insurance (NHI) is anticipated to improve the public availability of healthcare services. The study aims to investigate the role of NHI in hospital inpatient care in Indonesia. Methods: The analysis utilized data accessible via the 2023 National Socioeconomic Survey. This research used a cross-sectional design to investigate 1,223,377 individuals in total. Inpatient hospitalization was the outcome variable, while NHI membership was the exposure variable. As control variables, the research examined residence, age, gender, marital status, education, occupation, and wealth status. In the final phase of the investigation, multinomial logistic regression was utilized to assess the data. Results: According to the investigation, the hospital admission rate in Indonesia in 2023 was 2.41 %. Currently, 72.5 % of the population consists of NHI members. Regarding NHI membership, people with NHI are 2.76 times more likely than those without it (95 % CI 2.66–2.86). Furthermore, the study reports that seven control variables were associated with hospital inpatients in Indonesia in 2023: residence, age, sex, marital status, education, employment, and wealth status. Conclusions: The findings showed that NHI membership affects hospital inpatients in Indonesia. Membership in the NHI was associated with a nearly threefold increase in the likelihood of hospital inpatient care.